Strategic Support for Accounting for the Investment Process in the Innovation Industry - ASTANAKULOV, Olim T.; ASATULLAEV, Khurshid S.; SAIDSAIDAXMEDOVA, Nodira I.; ERGASHEV, Otamurod T. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
In modern conditions, the role and importance of investment policy pursued by machine-building enterprises are increasingly increasing. The purpose of the article is to study organizational-economic mechanism of formation of the investment policy companies. The author used General scientific and private methods of analysis; works of domestic and foreign scientists, monographs and lectures, periodicals, legislative and regulatory acts, statistical information. The scientific views on the management of the investment policy of the classics of economic thought are summarized, the investment theme is analyzed. It is concluded that the investment policy of machine-building enterprises is seen as a complex, interrelated and interdependent set of activities aimed at their further development. The algorithm of strategy of investment development of the machine-building enterprise of the region is offered. Given the specifics of the functioning of the engineering industry, the use of the algorithm will make it possible to identify factors that can affect the implementation of the investment project.